(untitled) (London, 2013)
The course takes a skills-based approach with each unit distinguishing between and global and close skills. The nature of each unit encourages students to think about the world around them, creating exciting and engaging learning material. The skills boxes that appear throughout the books signal the topic focus to the teacher, while providing the students with relevant tips, words and phrases.
Keywords: Tiếng Anh,English language,English language; Nghe,Listening,Spoken english